REFORMING THE EDUCATION SYSTEM IN UZBEKISTAN: PREPARING YOUNG SPECIALISTS FOR PROFESSIONAL EXCELLENCE - Allaev Sharofiddin Chori ogli (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation:  The main goal of this article is to reform the education system in Uzbekistan, to train young personnel, and to see measures in this direction.